Quebec Community Groups Network Congratulates Parties for Federal Election - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Urges English-speaking Quebecers to Vote for Best Local Candidate - Quebec Community Groups Network (QCGN) (2021)

QCGN Calls on Federal Parties and Candidates to Support the Language Rights of English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2021)

Neighbours of Rouyn-Noranda Guide to Federal Election Candidates for Abitibi-Téscamingue - Neighbours Regional Association of Rouyn-Noranda (2019)
Here is a brief guide to your candidates for the Abitibi-Témiscamingue riding, and some of the party platforms on key issues. Neighbours remains non-partisans and is only attempting to provide information not an endorsement.